A leaky integrate-and-fire model with adaptation for the generation of a spike train - Aniello Buonocore; Luigia Caputo; Enrica Pirozzi; Maria Francesca Carfora (Mathematical Biosciences and Engineering)
A model is proposed to describe the spike-frequency adaptation observed in many neuronal systems. We assume that adaptation is mainly due to a calcium-activated potassium current, and we consider two coupled stochastic differential equations for which an analytical approach combined with simulation techniques and numerical methods allow to obtain both qualitative and quantitative results about asymptotic mean firing rate, mean calcium concentration and the firing probability density. A related algorithm, based on the Hazard Rate Method, is also devised and described.